2007
DOI: 10.1029/2006ja012220
|View full text |Cite
|
Sign up to set email alerts
|

Structure and evolution of internal gravity waves and traveling ionospheric disturbances in regions with sharp gradients of the ionospheric parameters

Abstract: [1] The dynamics of the solitary nonlinear internal gravity waves (IGW), as well as traveling ionospheric disturbances (TID) of the electron density excited by IGW at the heights of the ionosphere's F region, for conditions close to those of the F layer assuming that the source of initial perturbation has the pulse character are studied. In particular, the cases when the solitary IGW and TID propagate in the regions with sharp gradients of the ionospheric parameters, such as electron density, temperature, scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The simulation of Millward et al [1993] indicated that one electric field burst could cause a single perturbation pulse of the LSTID and not a continuous wave train. Belashova et al [2007] suggested that the solitary gravity waves may have the shape of 2‐D solitons with single or oscillating asymptotics depending on the dispersive characteristics of the media. Thus both the source property and the background upper atmosphere characteristics are responsible for the forming of solitary LSTIDs.…”
Section: Statistical Resultsmentioning
confidence: 99%
“…The simulation of Millward et al [1993] indicated that one electric field burst could cause a single perturbation pulse of the LSTID and not a continuous wave train. Belashova et al [2007] suggested that the solitary gravity waves may have the shape of 2‐D solitons with single or oscillating asymptotics depending on the dispersive characteristics of the media. Thus both the source property and the background upper atmosphere characteristics are responsible for the forming of solitary LSTIDs.…”
Section: Statistical Resultsmentioning
confidence: 99%